Elementy kultury trzeciej oraz realia wojny afgańskiej w rosyjskim w przekładzie utworu Żmija Andrzeja Sapkowskiego - Dziwisz, Marcin (Acta Polono-Ruthenica, 2019)
This text focuses on the issue of war in Afghanistan from 1979–1989 and its realities. The lexicon associated with the everyday life of Afghanistan civilians and Soviet soldiers was analysed. The observations indicate that additional information appears more often in the translated text, which makes it much more transparent for the final recipient. This fact was confirmed by the statistical data, only one footnote can be found in the Polish text and 173 in the Russian text.